Biased Technological Progress, Factor Price Distribution, and Overcapacity: A Case from China - Peng Xiao; Baoxi Li; Yuhang He (Complexity)
This study aims to investigate the effects and mechanisms of biased technological progress on China’s industrial overcapacity. Using a time-varying stochastic frontier model, standardized supply-side system method, and the production function method, we measure the capacity utilization rate, biased technological progress index, and factor price distortion index in China’s industrial sector. Additionally, we employ a mediation effect model to analyze the impact of biased technological progress on overcapacity through factor price distortion. The findings suggest that biased technological progress can alleviate overcapacity, while factor price distortion exacerbates the problem. Biased technological progress alleviates overcapacity through capital price distortion, with a more significant effect in heavy industries than in light industries. Based on the results, we propose a series of policy recommendations, including optimizing the bias towards technological progress, improving the factor market, and enhancing the original innovation capability.